Wall surface anti-cracking material taking desulfurized gypsum as base material and preparation method of wall surface anti-cracking material

By using amylase to enzymatically dissolve tapioca starch and combined with expanded talc powder in wall crack-proof materials, the problems of uneven dispersion of talc powder and improper use of water reducers are solved, the crack resistance and strength are improved, and the water secretion rate is reduced. , realizes a more environmentally friendly and safe wall crack-proof material.

CN119285321APending Publication Date: 2025-01-10HUNAN MEIBI TU BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411500104.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

When using desulfurization gypsum to prepare wall crack-proof materials in the prior art, talc powder cannot be evenly dispersed, resulting in reduced crack resistance, and improper use of water reducing agents will lead to problems such as bubbles, long settling time and low strength.

Method used

Use cement and sand material and desulfurization gypsum to combine with amylase to enzymatically dissolve tapioca starch to form a porous structure, combine with expanded talc powder, reduce the floating of expanded talc powder, improve crack resistance, and consume free water in desulfurization gypsum through amylase, reducing The water content in the material should be avoided.

Benefits of technology

It significantly improves the crack resistance and strength of the wall crack-proof material, reduces the water secretion rate, avoids the problems caused by improper use of water reducing agents, and improves the environmental protection and safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285321A_ABST
    Figure CN119285321A_ABST
Patent Text Reader

Abstract

The invention discloses a wall surface anti-cracking material taking desulfurized gypsum as a base material and a preparation method of the wall surface anti-cracking material. The wall surface anti-cracking material is prepared from the following raw materials in parts by weight: 700 to 900 parts of desulfurized gypsum, 130 to 160 parts of cement, 700 to 900 parts of sand, 60 to 80 parts of latex powder, 0.5 to 2 parts of amylase, 1 to 2 parts of gypsum retarder, 5 to 7 parts of cellulose, 1 to 3 parts of cassava starch and 2 to 4 parts of expanded talcum powder. When the wall surface anti-cracking material is prepared, a water reducing agent is not needed, the use of the water reducing agent can be greatly reduced, and the wall surface anti-cracking material has the advantages of being more environmentally friendly, safer to use and lower in cost; the amylase is used, so that the anti-cracking performance of the material is greatly improved, cracks are effectively reduced, the bleeding rate is reduced, and the material has a wide market application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gypsum mortar preparation, and in particular to a wall anti-cracking material with desulfurized gypsum as a base material and a preparation method thereof. Background Art

[0002] Gypsum is a common plastering material for construction, and is widely used in wall crack prevention and other building decoration fields. With the continuous development of China's social economy, various wall crack prevention products have been developed at a high speed, which has greatly improved the preparation method of wall crack prevention materials. In the field of building decoration, wall cracking has always been a common problem. Due to temperature changes, foundation settlement and other reasons, cracks are prone to appear on the wall, affecting the beauty and service life of the building.

[0003] Desulfurized gypsum has similar properties to natural gypsum. It is gradually and widely used in the development of wall materials because of its advantages of energy saving, environmental protection, safety, good processing and construction performance, and durability. There are many studies in the prior art that use desulfurized gypsum as an aggregate base material for the preparation of wall anti-cracking materials, such as: Patent application number CN200710039970.2 is a method for preparing dry powder wall putty from desulfurized gypsum, wherein the components and their weight percentages are: desulfurized gypsum 65-80%, calcium enhancer 5-15%, powder filler 10-20%, composite activator 0.5-3%, binder 0.5-2%, retarder 0.1-0.2%, water retainer 0.2-0.5%, polypropylene fiber 0.05-0.15%; wherein the desulfurized gypsum is desulfurized gypsum discharged from coal-fired power plants, which is processed by low-temperature baking, powder (ball) grinding, whitening, high-temperature roasting and aging. The invention relates to a method for preparing desulfurized gypsum dry powder wall putty with desulfurized gypsum as the main raw material, which belongs to the technical field of comprehensive utilization of chemical building materials and solid waste. The components and weight percentages of the desulfurized gypsum dry powder wall putty of the present invention are: desulfurized gypsum 65-80%, calcium enhancer 5-15%, powdered filler 10-20%, composite activator 0.5-3%, binder 0.5-2%, retarder 0.1-0.2%, water retainer 0.2-0.5%, polypropylene fiber 0.05-0.15%. The desulfurized gypsum dry powder wall putty of the present invention uses desulfurized gypsum to replace natural gypsum to prepare desulfurized gypsum dry powder wall putty, which can reduce the cost of putty, make full use of resources, reduce the area of ​​desulfurized gypsum stacking, save precious land resources, achieve the dual effects of environmental protection and waste utilization, and can be firmly bonded to the base surface of the inner and outer walls of the building, and has the advantages of no cracking of the scraping coating, not easy to fall off, alkali resistance, water resistance, non-toxicity, and tastelessness. The wall putty (wall anti-cracking material) prepared by this method has the following problems: 1) Talc is added to the raw materials of this method to make the structure more stable and the crack resistance better. However, due to the small weight of talc, it will float when added to desulfurized gypsum, causing the talc to be unable to be evenly dispersed in the raw materials, which will greatly reduce the material's crack resistance; 2) The water reducer added to the raw materials used in this method can effectively improve the water seepage phenomenon when the material is used, but the dosage of the water reducer needs to be strictly controlled. Improper use of the water reducer can easily cause problems such as bubbles, long coagulation time, and low strength. In addition, some water reducers also contain chemical components that are harmful to the human body and the environment, causing significant adverse effects on the environment and human health.

[0004] In summary, how to provide a wall anti-cracking material with strong anti-cracking performance and can effectively reduce the use of water reducing agent has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a wall anti-cracking material based on desulfurized gypsum which can effectively improve crack resistance, reduce the amount of water reducing agent used, and greatly reduce water seepage rate.

[0006] The technical solution adopted by the present invention to solve the technical problem is: a wall anti-cracking material with desulfurized gypsum as a base material, comprising the following raw materials in parts by weight: 700-900 parts of desulfurized gypsum, 130-160 parts of cement, 700-900 parts of sand, 60-80 parts of latex powder, 0.5-2 parts of amylase, 1-2 parts of gypsum retarder, 5-7 parts of cellulose, 1-3 parts of cassava starch and 2-4 parts of expanded talc.

[0007] The wall anti-cracking material of the present invention uses desulfurized gypsum as a base material, and selects cement and sand materials in combination with desulfurized gypsum as aggregates. Since desulfurized gypsum, cement, sand materials and cellulose all have a certain bonding force, the compressive strength, flexural strength and tensile bonding strength of the wall anti-cracking material can be increased, making it difficult to be cracked; The use of amylase can slightly hydrolyze the cassava starch in the raw material, making the structure of the cassava starch looser and more porous, forming a network skeleton structure with a large number of pores inside, and increasing the specific surface area of ​​the cassava starch. It can not only effectively promote the combination of desulfurized gypsum and cellulose with the cassava starch, but also make the expanded talcum powder coated in the pores, effectively reducing the floating phenomenon of the expanded talcum powder, so that the expanded talcum powder is evenly dispersed in the raw material along with the porous structure of the cassava starch, greatly improving the anti-cracking performance of the wall anti-cracking material; at the same time, the used expanded talcum powder has a more porous structure than talcum powder, which can further increase its contact area with other raw materials, further improve the anti-cracking effect of the wall anti-cracking material, and have better strength.

[0008] In addition, when the cassava starch of the present invention is enzymolyzed under the action of amylase, the free water in the desulfurized gypsum can be consumed, which greatly reduces the content of free water in the desulfurized gypsum, and further reduces the water content in the wall anti-cracking material, so that there is no need to use a water reducer in the raw materials of the wall anti-cracking material of the present invention, and the water seepage rate of the wall anti-cracking material when it is used can be effectively reduced, and the problems of bubbles, long coagulation time, low strength, etc. caused by improper use of the water reducer are effectively avoided, so that the wall anti-cracking material of the present invention is more environmentally friendly and safer to use.

[0009] Preferably, the wall anti-cracking material comprises the following raw materials in parts by weight: 800 parts of desulfurized gypsum, 140 parts of cement, 800 parts of sand, 70 parts of latex powder, 1 part of amylase, 1.6 parts of gypsum retarder, 6 parts of cellulose, 2 parts of cassava starch, and 3 parts of expanded talc.

[0010] Furthermore, the enzymatic activity of the amylase is 12000-14000 U / g.

[0011] Furthermore, the cement is 425 white cement, and the particle size of the sand is 90 mesh.

[0012] The present invention also provides a method for preparing the wall anti-cracking material based on desulfurized gypsum as described above, comprising the following steps: 1) Place cassava starch and desulfurized gypsum in a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer, adjust the pH to 5.0-6.0, and stir in a water bath for 10-20 minutes to prepare a starch suspension; then add amylase to the starch suspension, continue stirring and enzymolysis for 24 hours, wash with deionized water until neutral, and then freeze-dry to obtain a premix; 2) Mix the premix, cement, sand, latex powder, gypsum retarder, cellulose and expanded talcum powder evenly. Get wall anti-cracking materials.

[0013] Furthermore, in step 1), the volume ratio of the total mass of cassava starch and desulfurized gypsum to the volume of disodium hydrogen phosphate-sodium dihydrogen phosphate buffer is 1:100-150, and the water bath temperature is 40-50°C. Furthermore, the preparation method of the expanded talc powder is: sending the talc powder into a heating furnace at a temperature of 250-280° C. for heating for 1-2 hours; and then sending the talc powder into an expansion furnace at a temperature of 500-600° C. for rapid roasting for 30-45 seconds.

[0014] Furthermore, the stirring time in step 2) is 60 min, and the stirring speed is 180-220 r / min.

[0015] Beneficial effects of the wall anti-cracking material based on desulfurized gypsum and the preparation method thereof of the present invention: (1) The preparation method of the present invention is simple. No water reducer is required when preparing the wall anti-cracking material. The present invention can also achieve a good effect of reducing water seepage rate. Compared with the wall anti-cracking material containing a water reducer in the prior art, the use of the water reducer can be greatly reduced. The present invention has the advantages of being more environmentally friendly, safer to use and lower cost. (2) The wall anti-cracking material of the present invention can effectively promote the combination of cassava starch with desulfurized gypsum, cellulose and expanded talcum powder by using amylase, reduce the floating phenomenon of expanded talcum powder, and make the expanded talcum powder dispersed more evenly in the raw materials, thereby greatly improving the anti-cracking performance of the wall anti-cracking material and effectively reducing the occurrence of cracks; and the use of amylase can also consume the free water in the desulfurized gypsum, so that the internal moisture in the mortar can be effectively consumed, which can greatly reduce the water seepage rate; (3) The expanded talc used in the present invention has a more porous structure than talc, which can further increase its contact area with other raw materials, further improve the anti-cracking effect of the wall anti-cracking material, and have better strength; (4) The wall anti-cracking material of the present invention can be widely used in the decoration projects of the interior and exterior walls of buildings, has broad market application prospects, and has significant technical advantages and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 — is a process flow chart of a method for preparing a wall anti-cracking material based on desulfurized gypsum according to the present invention. DETAILED DESCRIPTION

[0017] The present invention is further described below in conjunction with the accompanying drawings and examples, but these specific implementation schemes do not limit the protection scope of the present invention in any way.

[0018] In the present invention, parts by weight may be μg, mg, g, kg or other weight units known in the art, and kg is used in the following examples.

[0019] Example 1 A method for preparing a wall anti-cracking material based on desulfurized gypsum, the process flow chart of which is as follows Figure 1 As shown, the following steps are included: 1) 2 kg of cassava starch and 800 kg of desulfurized gypsum are placed in a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution, the volume ratio of the total mass of cassava starch and desulfurized gypsum to the disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution is 1:100, the pH is adjusted to 5.0-6.0, and the starch suspension is prepared by stirring for 15 minutes at a water bath temperature of 45°C; then 1 kg of amylase with an activity of 14000 U / g is added to the starch suspension, and the enzymolysis is continued by stirring for 24 hours, and the mixture is washed with deionized water until neutral, and then freeze-dried to obtain a premix; 2) Mix the premix, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder, 6 kg of cellulose and 3 kg of expanded talcum powder, and stir at a speed of 220 r / min for 60 min to mix the raw materials evenly to obtain the wall anti-cracking material.

[0020] The preparation method of the expanded talc powder is as follows: the talc powder is sent into a heating furnace at a temperature of 260° C. for heating for 1.5 hours; and then sent into an expansion furnace at a temperature of 550° C. for rapid roasting for 40 seconds.

[0021] The raw material ratio of the wall anti-cracking material in this embodiment is: 800 kg of desulfurized gypsum, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1 kg of amylase, 1.6 kg of gypsum retarder, 6 kg of cellulose, 2 kg of cassava starch, and 3 kg of expanded talc.

[0022] Example 2 The raw material ratio of the wall anti-cracking material in this embodiment is: 700 kg of desulfurized gypsum, 130 kg of 425 white cement, 700 kg of 90 mesh sand, 60 kg of latex powder, 0.5 kg of amylase, 1 kg of gypsum retarder, 5 kg of cellulose, 1 kg of cassava starch, and 2 kg of expanded talc. The preparation method of the wall anti-cracking material is the same as that of Example 1.

[0023] Example 3 The raw material ratio of the wall anti-cracking material in this embodiment is: 900 kg of desulfurized gypsum, 160 kg of 425 white cement, 900 kg of sand material, 80 kg of latex powder, 2 kg of amylase, 2 kg of gypsum retarder, 7 kg of cellulose, 3 kg of cassava starch, and 4 kg of expanded talc. The preparation method of the wall anti-cracking material is the same as that of Example 1.

[0024] The raw material ratio table of the wall anti-cracking material of Examples 1-3 is shown in the following table: Table 1 Raw material ratios of wall anti-cracking materials of Examples 1-3

[0025] The present invention refers to the method of "GB / T 28627-2023 Plastering Gypsum" to measure the setting time, compressive strength, flexural strength, tensile bond strength and water retention rate of the wall anti-cracking material prepared in Examples 1-3; at the same time, the water bleeding rate of the wall anti-cracking material is also measured. The water bleeding is to pour the wall anti-cracking material of equal volume after mixing into a container of a certain shape and volume. After the wall anti-cracking material starts to bleed, the water is sucked out and the volume is weighed. The volume ratio of the accumulated water bleeding to the amount of water used to mix the wall anti-cracking material is the water bleeding rate. The results are shown in Table 2: Table 2 Test results of various performance indicators of wall anti-cracking materials of Examples 1-3

[0026] It can be seen from Table 2 that the setting time, water retention rate and strength of the wall anti-cracking material prepared by the present invention all meet the standards of heavy plaster (bottom plaster), and the water seepage rate is less than 3%, which can effectively reduce the water seepage of the wall anti-cracking material.

[0027] Comparative Example 1 The raw material ratio of the wall anti-cracking material in this comparative example is: 800 kg of desulfurized gypsum, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder, 7 kg of cellulose, and 2 kg of cassava starch.

[0028] The preparation method of the wall anti-cracking material is as follows: 800 kg of desulfurized gypsum, 140 kg of 425 white cement, 800 kg of 90-mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder, 6 kg of cellulose and 2 kg of cassava starch are mixed, and the mixture is stirred at a speed of 220 r / min for 60 minutes to uniformly mix the raw materials, so as to obtain the wall anti-cracking material.

[0029] Comparative Example 2 800kg desulfurized gypsum, 140kg 425 white cement, 800kg 90-mesh sand, 70kg latex powder, 1.6kg gypsum retarder, 6kg cellulose, 2kg cassava starch and 3kg expanded talc.

[0030] The preparation method of the wall anti-cracking material comprises the following steps: mixing 800 kg of desulfurized gypsum, 140 kg of 425 white cement, 800 kg of 90-mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder, 6 kg of cellulose, 2 kg of cassava starch and 3 kg of expanded talcum powder, stirring for 60 minutes at a speed of 220 r / min to uniformly mix the raw materials, and obtaining the wall anti-cracking material.

[0031] Comparative Example 3 800kg desulfurized gypsum, 140kg 425 white cement, 800kg 90-mesh sand, 70kg latex powder, 1kg amylase, 1.6kg gypsum retarder, 6kg cellulose and 2kg cassava starch.

[0032] The preparation method of the wall anti-cracking material comprises the following steps: 1) 2 kg of cassava starch and 800 kg of desulfurized gypsum are placed in a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution, the volume ratio of the total mass of cassava starch and desulfurized gypsum to the disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution is 1:100, the pH is adjusted to 5.0-6.0, and the starch suspension is prepared by stirring for 15 minutes at a water bath temperature of 45°C; then 1 kg of amylase with an activity of 14000 U / g is added to the starch suspension, and the enzymolysis is continued by stirring for 24 hours, and the mixture is washed with deionized water until neutral, and then freeze-dried to obtain a premix; 2) Mix the premix, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder and 6 kg of cellulose, and stir at a speed of 220 r / min for 60 min to mix the raw materials evenly to obtain the wall anti-cracking material.

[0033] Comparative Example 4 800kg desulfurized gypsum, 140kg 425 white cement, 800kg 90 mesh sand, 70kg latex powder, 1kg amylase, 1.6kg gypsum retarder, 6kg cellulose, 2kg cassava starch and 3kg talcum powder.

[0034] The preparation method of the wall anti-cracking material comprises the following steps: 1) 2 kg of cassava starch and 800 kg of desulfurized gypsum are placed in a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution, the volume ratio of the total mass of cassava starch and desulfurized gypsum to the disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution is 1:100, the pH is adjusted to 5.0-6.0, and the starch suspension is prepared by stirring for 15 minutes at a water bath temperature of 45°C; then 1 kg of amylase with an activity of 14000 U / g is added to the starch suspension, and the enzymolysis is continued by stirring for 24 hours, and the mixture is washed with deionized water until neutral, and then freeze-dried to obtain a premix; 2) Mix the premix, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1.6 kg of gypsum retarder, 6 kg of cellulose and 3 kg of talcum powder, and stir at a speed of 220 r / min for 60 min to mix the raw materials evenly to obtain the wall anti-cracking material.

[0035] Comparative Example 5 800kg desulfurized gypsum, 140kg 425 white cement, 800kg 90-mesh sand, 70kg latex powder, 1kg amylase, 1kg water reducer, 1.6kg gypsum retarder, 6kg cellulose, 2kg cassava starch and 3kg expanded talc.

[0036] The preparation method of the wall anti-cracking material comprises the following steps: 1) 2 kg of cassava starch and 800 kg of desulfurized gypsum are placed in a disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution, the volume ratio of the total mass of cassava starch and desulfurized gypsum to the disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution is 1:100, the pH is adjusted to 5.0-6.0, and the starch suspension is prepared by stirring for 15 minutes at a water bath temperature of 45°C; then 1 kg of amylase with an activity of 14000 U / g is added to the starch suspension, and the enzymolysis is continued by stirring for 24 hours, and the mixture is washed with deionized water until neutral, and then freeze-dried to obtain a premix; 2) Mix the premix, 140 kg of 425 white cement, 800 kg of 90 mesh sand, 70 kg of latex powder, 1 kg of water reducer, 1.6 kg of gypsum retarder, 6 kg of cellulose and 3 kg of talcum powder, and stir at a speed of 220 r / min for 60 min to mix the raw materials evenly to obtain the wall anti-cracking material.

[0037] The raw material ratios of the wall anti-cracking materials of Example 1 and Comparative Examples 1-5 are shown in the following table: Table 3 Raw material ratios of wall anti-cracking materials of Example 1 and Comparative Examples 1-5

[0038] The present invention also measured the setting time, compressive strength, flexural strength, tensile bond strength, water retention rate and water bleeding rate of the wall anti-cracking materials prepared in Comparative Examples 1-5. The results are shown in Table 4: Table 4 Test results of various performance indicators of wall anti-cracking materials of Example 1 and Comparative Examples 1-5

[0039] It can be seen from the above table that the wall anti-cracking material (Example 1) of the present invention has better flexural strength, tensile strength, tensile bonding strength and water bleeding rate than comparative examples 1-5, and its various indicators are significantly better than comparative example 1, and the strength of comparative example 1 is lower than that of comparative example 2 and comparative example 3, indicating that there is an interaction and coordination relationship between amylase, expanded talc and other raw materials. The lack of any one of the raw materials in amylase or expanded talc will have a significant impact on the anti-cracking performance of the wall anti-cracking material.

[0040] Compared with Example 1, the strength and water seepage rate of the wall anti-cracking material prepared in Comparative Example 2 are significantly lower than those in Example 1. Comparative Example 2 is prepared by removing amylase from the raw materials of Example 1, which shows that the addition of amylase can not only effectively improve the strength of the wall anti-cracking material, so that the wall anti-cracking material has better anti-cracking performance, but also can effectively reduce the water seepage rate, so that the water seepage phenomenon of the wall anti-cracking material is greatly reduced. This may be because amylase can slightly hydrolyze cassava starch, making the structure of cassava starch looser and forming a network skeleton structure with a large number of pores inside, thereby increasing the specific surface area of ​​cassava starch. This can not only effectively promote the combination of desulfurized gypsum and cellulose with cassava starch, but also allow the expanded talc to be coated in the pores, effectively reducing the floating phenomenon of the expanded talc, and allowing the expanded talc to be evenly dispersed in the raw materials along with the porous structure of the cassava starch, further improving the strength of the wall anti-cracking material, thereby greatly improving the anti-cracking performance of the wall anti-cracking material; in addition, the hydrolysis of cassava starch under the action of amylase can consume the free water inside the desulfurized gypsum, thereby greatly reducing the water seepage rate of the wall anti-cracking material.

[0041] Compared with Example 1, the strength of the wall anti-cracking materials prepared in Comparative Examples 3 and 4 is lower than that in Example 1, especially the compressive strength shows a significant difference. Comparative Example 3 is prepared by removing the expanded talcum powder from the raw materials of Example 1, and Comparative Example 4 is prepared by replacing the expanded talcum powder with talcum powder on the basis of the raw materials of Example 1, indicating that the addition of expanded talcum powder can effectively improve the strength of the wall anti-cracking material, and the effect of expanded talcum powder on improving the strength of the wall anti-cracking material is more significant than that of talcum powder. It may be because the expanded talcum powder used has a more porous structure than talcum powder, which can further increase its contact area with other raw materials, thereby improving the strength of the wall anti-cracking material, so that the wall anti-cracking material has a better anti-cracking effect.

[0042] Compared with Example 1, there is no significant difference in the setting time, water retention rate, strength and water seepage rate of the wall anti-cracking material prepared in Comparative Example 5, but Comparative Example 5 adds the use of a water reducer on the basis of the raw materials in Example 1, and its corresponding water seepage rate is the same as that in Example 1, indicating that the present invention can achieve the same effect of adding a water reducer without adding a water reducer. This may be because the added amylase consumes the free water in the desulfurized gypsum when hydrolyzing the cassava starch, so that the internal moisture in the wall anti-cracking material is effectively consumed, reducing the internal moisture in the wall anti-cracking material, thereby reducing the rate and amount of internal moisture lost to the environment, so that the prepared wall anti-cracking material has a lower water seepage rate.

[0043] Experimental example In this experimental example, the wall anti-cracking material was prepared by referring to the raw material composition and method of Example 1, and the effects of different amylase activities (8000 U / g, 10000 U / g, 12000 U / g, 14000 U / g, 16000 U / g) on ​​the strength and water seepage rate of the wall anti-cracking material were studied. The results are shown in Table 5.

[0044] Table 5 Effects of different amylase activities on the strength and water seepage rate of wall anti-cracking materials

[0045] It can be seen from the above table that with the increase of the enzyme activity of amylase, when the enzyme activity is between 8000 and 14000 U / g, the strength of the wall anti-cracking material shows an increasing trend, and the water bleeding rate shows a decreasing trend; when the enzyme activity continues to increase to 16000 U / g, the strength of the wall anti-cracking material shows a decreasing trend, and the water bleeding rate shows an increasing trend. This may be because too high an enzyme activity will cause excessive hydrolysis of cassava starch, resulting in the collapse of the spatial structure of cassava starch, thereby reducing the strength and increasing the water bleeding rate; and when the enzyme activity is 12000 U / g and 14000 U / g, there is no significant difference in the corresponding strength and water bleeding rate, and the optimal effect is 14000 U / g. Therefore, when the enzyme activity of amylase is most preferably 14000 U / g, it can not only make the wall anti-cracking material have better strength, but also effectively prevent the occurrence of water bleeding, so that the wall anti-cracking material has better crack resistance.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A wall anti-cracking material based on desulfurized gypsum, characterized in that: The invention comprises the following raw materials in parts by weight: 700-900 parts of desulfurized gypsum, 130-160 parts of cement, 700-900 parts of sand material, 60-80 parts of latex powder, 0.5-2 parts of amylase, 1-2 parts of gypsum retarder, 5-7 parts of cellulose, 1-3 parts of cassava starch and 2-4 parts of expanded talc.

2. A wall anti-cracking material based on desulfurized gypsum as claimed in claim 1, characterized in that: The gypsum mortar comprises the following raw materials in parts by weight: 800 parts of desulfurized gypsum, 140 parts of cement, 800 parts of sand, 70 parts of latex powder, 1 part of amylase, 1.6 parts of gypsum retarder, 6 parts of cellulose, 2 parts of cassava starch and 3 parts of expanded talc.

3. A wall anti-cracking material based on desulfurized gypsum as claimed in claim 1, characterized in that: The enzymatic activity of the amylase is 12000-14000 U / g.

4. The wall anti-cracking material based on desulfurized gypsum as claimed in claim 1, characterized in that: The cement is 425 white cement, and the particle size of the sand is 90 mesh.

5. A method for preparing a wall anti-cracking material based on desulfurized gypsum as claimed in claims 1-4, characterized in that: The following steps are involved: 1) Place cassava starch and desulfurized gypsum in disodium hydrogen phosphate-sodium dihydrogen phosphate buffer, adjust the pH to 5.0-6.0, and stir in a water bath for 10-20 minutes to prepare a starch suspension; Then add amylase to the starch suspension, continue stirring and enzymolysis for 24 hours, wash with deionized water until neutral, and then freeze-dry to obtain a premix; 2) Mix the premix, cement, sand, latex powder, gypsum retarder, cellulose and expanded talcum powder evenly. Get wall anti-cracking material.

6. A method for preparing a wall anti-cracking material based on desulfurized gypsum as claimed in claim 5, characterized in that: In the step 1), the volume ratio of the total mass of cassava starch and desulfurized gypsum to the disodium hydrogen phosphate-sodium dihydrogen phosphate buffer solution is 1:100-150, and the water bath temperature is 40-50°C.

7. A method for preparing a wall anti-cracking material based on desulfurized gypsum as claimed in claim 5, characterized in that: The preparation method of the expanded talc powder is as follows: the talc powder is sent into a heating furnace at a temperature of 250-280° C. to be heated for 1-2 hours; and then sent into an expansion furnace at a temperature of 500-600° C. to be rapidly roasted for 30-45 seconds.

8. A method for preparing a wall anti-cracking material based on desulfurized gypsum as claimed in claim 5, characterized in that: The stirring time in step 2) is 60 min, and the stirring speed is 180-220 r / min.

Citation Information

Patent Citations

  • Method for preparing powder wall mastic with desullfurization gypsum

    CN101037557A